Determining population-specific risk factors for COVID-19 susceptibility and severity to inform future individual-level integrated risk scoring - Ilham Morani; Haneen Shibli; David Karasik; Michael Edelstein (BMC Infectious Diseases)
Abstract Objectives Acute respiratory tract infections (ARI), including COVID-19, are a significant global health challenge with pandemic potential. Understanding factors influencing ARI susceptibility and severity in different populations is crucial for pandemic preparedness and mitigation. We investigated epidemiological risk factors for COVID-19 susceptibility and severity in the Israeli population. Methods Participants who took a COVID-19 PCR test between July 2021 and August 2022 completed an online survey including demographics, comorbidities, infection and vaccination status. We identified factors associated with SARS-CoV-2 infection and disease severity using logistic regression and compared our results with the global literature. Results We included 2128 participants. Of these 823 participants were tested positive for SARS-CoV-2. Individuals without COPD and BMI > 30 had higher infection odds (aOR = 6.21, 95% CI:1.42–27.25 and aOR = 1.54, 95% CI:1.02–2.32; respectively). High school-level education was associated with increased susceptibility and severity compared to higher education (aOR = 1.55, 95% CI:1.1–2.18 and aOR = 2.80, 95% CI 1.62–4.86; respectively). Hospitalization was associated with older age (p < 0.001). Vaccination with 3 doses significantly reduced infection and hospitalization risk compared to unvaccinated (aOR = 0.024, 95% CI:0.016–0.04 and aOR = 0.37, 95% CI: 0.17–0.81; respectively, p < 0.05). Compared to Arab participants, Jewish ones were less likely to be infected (aOR = 1.48, 95% CI:1.02–2.15, p < 0.05). Conclusions Identified risk factors are consistent with meta-analyses of studies from other countries. Similar to other countries, minority groups were found to be at higher risk, therefore risk models predicting ARI susceptibility and severity have to take this into account.